Antimicrobial Properties of Essential Oil Extracted from Azadirachta indica Leaves on Common Skin Pathogens - Geetha, Subramaniam; Nur Husnina, Bazilah Rafeny; Lalita Ambigai, Sivasamugham (INTI International University, 2019)
Antibiotic resistance is rising to dangerously high levels and spreading globally at an alarming rate mainly due to misuse and over prescription of antibiotics. Hence, scientists are studying medicinal plants to find potential alternatives in reducing the antibiotic resistance. In this study, Azadirachta indica essential oil was extracted from dried leaves due to several findings reported that the phytochemicals present in A. indica leaves had the ability to treat common skin pathogens including Staphylococcus aureus, Staphylococcus epidermidis, Propionibacterium acnes, methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant Staphylococcus epidermidis (MRSE). The results showed that the extracted A. indica essential oil had better antimicrobial effects on MRSA and MRSE compared to cefoxitin as a reference point. The extracted oil also had significant antimicrobial activity when tested against P. acnes. Stability of the extracted essential oil was studied to confirm the stability of phytochemicals in the extracted A. indica essential oil at 4ºC for a month and the results were similar to the freshly extracted A. indica essential oil.